An enhancement of stroke width transform algorithm applied in text detection in images - John Delfin Aquilo, Charlyne Mary Francisco. 4 0 16; 5
ABSTRACT One of the most important parts of image information retrieval is text detection in images. In this research, we present a novel image operator that seeks to find the value of stroke width for each image pixel, and demonstrate its use on task of text detection in images that is called the Stroke Width Transform which is commonly used in image processing. The system applies text detection in images using SWT Algorithm. The algorithm has issues in its results wherein the detected texts have broken letters and noises, it doesn't detect some letters of a word or some words present in the image that are small, narrow or have noises surrounding it, and it cannot detect cursive texts/letters. The enhanced SWT algorithm solves the problem by double threshold and hysteresis, removing connected-components algorithm in finding letter candidates and tracing of edges horizontally, vertically and diagonally.
Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2